Mechanism of hepatotoxicity induced by ethanol extract of Emilia sonchifolia (L.) DC revealed by proteomics and metabolomics - Chen, Gongzhen; Luo, Qiantonghan; Song, Zicong; Zheng, Ping; Liu, Xin; Tang, Ting (Frontiers in Pharmacology, 2025)
ObjectiveHepatotoxicity has been reported for Emilia sonchifolia (L.) DC (E. sonchifolia). The plant material is typically prepared using two extraction methods for practical application: water extraction and ethanol extraction. However, our previous research only investigated its water extract. Therefore, this study aims to systematically evaluate the hepatotoxicity and underlying mechanisms of the ethanol extract of E. sonchifolia, thereby providing a more comprehensive scientific basis for its rational application and safety assessment.MethodsAn acute toxicity preliminary screening study was conducted by orally administering E. sonchifolia ethanol extract to mice at doses ranging from 0 to 33.6 g/kg/day. Based on the results of the acute toxicity test preliminary screening study, mice were divided into a control group and an E. sonchifolia ethanol extract group (8.6 g/kg/day) for a 14-day delayed hepatotoxicity experiment based on clinical treatment duration. At the end of the intervention, hepatic pathological changes were examined using hematoxylin-eosin staining. Enzyme-linked immunosorbent assay (ELISA) was employed to quantify the levels of alanine aminotransferase, aspartate aminotransferase, total bilirubin, direct bilirubin, total bile acids, alkaline phosphatase, and γ-glutamyl transferase in serum, as well as malondialdehyde, superoxide dismutase, and catalase in liver tissue. Proteomics and metabolomics analyses were performed to investigate the mechanisms of hepatotoxicity induced by the ethanol extract. Additionally, the mRNA expression levels of Cyp3a41a, Cyp2c29, Ugt2b1, and Hsd3b3 in mice liver tissue were determined using quantitative reverse transcription polymerase chain reaction (qRT-PCR).ResultsThe acute toxicity preliminary screening study results showed that a dose of 12.0 g/kg or higher of the E. sonchifolia ethanol extract caused acute liver failure and death in mice. A dose of 8.6 g/kg or lower of the E. sonchifolia ethanol extract produced dose-dependent acute hepatotoxicity. Meanwhile, a dose of 8.6 g/kg of the E. sonchifolia ethanol extract induced delayed toxicities in mice. Proteomics and metabolomics results revealed that the hepatotoxicity induced by the ethanol extract of E. sonchifolia was associated with cholestasis and oxidative stress caused by disruptions in drug metabolism, steroid hormone biosynthesis, and primary bile acid biosynthesis. Validation experiments showed that the levels of Cyp2c29 were decreased, while the mRNA levels of Cyp3a41a, Ugt2b1, and Hsd3b3 were increased in the liver tissues of mice treated with the ethanol extract of E. sonchifolia. Additionally, serum levels of total bilirubin, direct bilirubin, total bile acids, alkaline phosphatase, and γ-glutamyl transferase were significantly elevated. Furthermore, in the livers of mice treated with the ethanol extract, malondialdehyde levels were increased, whereas superoxide dismutase and catalase levels were decreased.ConclusionIn summary, the ethanol extract of E. sonchifolia can induce hepatotoxicity in mice, and its mechanism is associated with cholestasis and oxidative stress mediated by disruptions in drug metabolism, steroid hormone biosynthesis, and primary bile acid biosynthesis.